MONOPOLY GAME AS ANDROID-BASED DENTAL HEALTH EDUCATION MEDIA - Santoso, Bedjo; Anwar, M. Choiroel; Muliadi, Muliadi (Postgraduate Program , Poltekkes Kemenkes Semarang, 2019)
Background: The problem of dental hygiene and many encounter is dental caries and periodontal disease. These problems can be prevented through the dental health education. Literatur this review aims to generate dental health education media in the form of an application-based games to android Method: Research and Development/(R&D) and quasi experimental non-randomized control group pretes and post-test design (non-equivalent control group). The result: a test of wilcoxon test on the main field shows the difference between the value of the knowledge and attitude of intervention and control group is Z:-Sig: 6.006 value 0.000 and Z: 863-4, with a value of Sig: 0.000 (value of knowledge), Z:-value of 6.412 Sig: 0.000 and Z:- 4.558 value Sig: 0.000 (attitude). Mannwhitney test showed the value of the difference between knowledge and attitudes of the intervention group and the control i.e. z:4.868 with value Sig: 0.000 and value Z: 4.641-value Sig: 0.000. Conclusion: the Game monopoly and leaflets as a dental health education media were equally effective in increasing knowledge and attitude of dental health. However, the game monopoly is more effective than leaflets.